2018
DOI: 10.1136/bcr-2018-224529
|View full text |Cite
|
Sign up to set email alerts
|

Marantic endocarditis: incidental infarcts leading to diagnosis of pancreatic cancer

Abstract: Non-bacterial thrombotic endocarditis (NBTE) is a well-described phenomenon associated with malignancies due to hypercoaguable state. In the setting of pancreatic cancer, NBTE is more commonly diagnosed postmortem. We describe a case of a man who was diagnosed with pancreatic carcinoma after incidental finding of NBTE. Imaging incidentally revealed multiple strokes, bilateral renal and splenic infarcts, while subsequent workup for cardioembolic source demonstrated a 1.1×0.7 cm mitral valve vegetation. As multi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
5
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 12 publications
1
5
0
Order By: Relevance
“…Although, transoesophageal echocardiogram (TOE) is more sensitive than TTE, two-dimensional TTE is the first choice with TOE reserved for cases where TTE is unrevealing, with suitable patients 1. Our echocardiographic findings are consistent with the findings of previously published cases 8 18…”
Section: Discussionsupporting
confidence: 92%
“…Although, transoesophageal echocardiogram (TOE) is more sensitive than TTE, two-dimensional TTE is the first choice with TOE reserved for cases where TTE is unrevealing, with suitable patients 1. Our echocardiographic findings are consistent with the findings of previously published cases 8 18…”
Section: Discussionsupporting
confidence: 92%
“…The flow chart of our included studies is shown in Supplementary Figure S1 . Around 25% (39) of included studies were from the USA, and only 1 study was reported from China [ 19 , 22 , 23 , 24 , 27 , 29 , 32 , 33 , 34 , 39 , 41 , 43 , 46 , 47 , 48 , 57 , 58 , 59 , 68 , 69 , 73 , 76 , 81 , 84 , 86 , 88 , 92 , 93 , 94 , 100 , 101 , 105 , 108 , 111 , 114 , 115 , 118 , 131 , 132 , 136 ]. A list of the included studies and the quality assessment are reported in Supplementary Table S2 .…”
Section: Resultsmentioning
confidence: 99%
“…In general, the prognosis of marantic endocarditis is good, as the vegetations are usually small and do not typically cause significant damage to the heart valves. Many patients with marantic endocarditis do not experience symptoms, and the condition may be discovered incidentally on an echocardiogram or in other imaging studies [ 118 , 158 ]. However, as we mentioned before, in some cases, the vegetations can cause emboli that can result in serious complications such as stroke, heart attack, or organ damage [ 31 , 69 , 74 ].…”
Section: Discussionmentioning
confidence: 99%
“…In this unique process, the valvular tissue involved is typically normal or with a minimal exhibition of abnormal elastic fibers or collagen [2] . NBTE has been associated with proinflammatory scenarios such as malignancy, where inflammation releases both interleukin-1 (IL-1) and tumor necrosis factor (TNF) which act toward damaging tissue, leading to thrombus deposition [6] . In contrast to bacterial IE, these patients are found to have an absence of bacteremia [2] .…”
Section: Discussionmentioning
confidence: 99%